The Numerical Study on the Multi-Stage Cold Forming Process of Hexalobular Socket Torx Nuts - Yang, Chih-Cheng; Lu, Jian-Qing; Tsai, Hsiu Ying; Andres, Jhonel Cortez (European Journal of Applied Sciences, 2025)
In this study, a multi-stage cold forming process for the manufacture of hexalobular socket Torx nuts is studied numerically with AISI 1022 carbon steel. The cold forming process through four stages includes preparation and centering for backward extrusion, backward extrusion over die pin, upsetting operation, and backward extrusion to form a hexalobular socket over a punch pin. The numerical simulations of cold forming are carried out using the finite element code of DEFORM-3D. The formability of the workpiece is studied, such as the effect on forming force responses, maximum forming forces, effective stress and strain distributions and metal flow pattern. In the four-stage forming process, in the stages of upsetting and backward extrusion over a moving punch to form a hexalobular socket cavity, the effective stresses in the head of the workpiece are significantly high, and the effective strains are also significantly high due to large deformation. The flow line distributions are also very complex in which the flow lines in the regions of upsetting and backward extruding a hexalobular socket cavity at the head of workpiece are severely bent, highly compacted. For the first stage, the maximum axial forming force of 164.3 kN is the greatest of the four stages, which the workpiece is flattened and centered; while the forming energy of 39.9 J is the smallest of the four stages due to the shortest acted axial forging stroke. However, in the second stage of backward extrusion over a punch tool mounted in the die, the maximum forming force of 55.7 kN is the smallest of the four stages; while the forming energy of 263.6 J is the greatest of the four stages due to the longer acted axial forming stroke. The total maximum axial forming forces from the first to the last stages are 413.5 kN and the total forming energies are about 0.56 kJ.